Institutional Liquidity Costs, Internalized Retail Trade Imbalances, and the Cross Section of Stock Returns - Barardehi, Yashar H.; Bernhardt, Dan; Da, Zhi; Warachka, Mitch (Journal of Financial and Quantitative Analysis, 2025)
Abstract Order flow segmentation prevents direct interactions between U.S. retail and institutional investors. Using the imbalance in observable internalized retail trades, we show wholesalers use retail flow to provide liquidity to institutional investors, especially when liquidity is scarce. Our institutional liquidity cost ( $ ILC $ ) measures average absolute retail trade imbalances, positing that institutions holding stocks with greater such averages more often resort to the expensive wholesaler-provided liquidity. $ ILC $ is correlated with expected institutional price impacts. Unlike existing illiquidity measures, $ ILC $ has economically meaningful relations with institutional holding horizons and yields annualized liquidity premia of 2.7%–3.2% post-2010, even after excluding microcap stocks.